Case report: False-positive B-type natriuretic peptide results with the cyclic amplified fluorescence immunoassay - Qian Yin; Fei Wang; Chen Zhang; Yi-bin Pan (Journal of International Medical Research)
B-type natriuretic peptide, which was initially isolated from porcine brain tissue, has been used in the clinic as an important indicator for the diagnosis, risk stratification, and prognosis of heart failure. In recent years, many commercial immunoassays to assess B-type natriuretic peptide have been reported to undergo interference due to various factors. At present, the commonly used assays to assess B-type natriuretic peptide are enzyme-linked immunosorbent assay and direct chemiluminescence, which are based on a “sandwich structure” formed by dual antibodies; both assays have been reported to undergo interference. We report the case of a patient whose B-type natriuretic peptide results, which were detected using a cyclic amplified fluorescence immunoassay, were false-positive. The patient had a low-risk pulmonary embolism without right heart failure; however, her B-type natriuretic peptide results were surprisingly high. Further study confirmed that the abnormal B-type natriuretic peptide result was caused by the interference of the human anti-mouse antibodies. Therefore, when encountering B-type natriuretic peptide results that are not consistent with the clinical situation, the possibility of interference in the assay should be considered.